Successful Endoscopic Management of Bile Leak: A Single-Center Experience - Pawar, Vinay; Sonthalia, Nikhil; Pawar, Sunil; Surude, Ravindra; Contractor, Qais; Rathi, Pravin (Journal of Digestive Endoscopy, 2017)
Background and Aims: Bile leak is a rarely encountered complication most commonly occurring in the setting of biliary tract surgery. Site of leak may be from the gallbladder bed, the cystic duct, or rarely from injury to a major bile duct. Management has evolved with from radical surgery prevalent in earlier days to recent increased expertise in biliary endoscopy. This study aims to determine the impact of endoscopic management in treating symptomatic bile leak and discusses the role of surgery. Patients and Methods: In this retrospective study, patients with symptomatic bile leak admitted between 2012 and 2015 to the Department of Gastroenterology of a tertiary care center in Western India were analyzed. Site and extent of bile leak was evaluated using contrast enhanced computed tomography or magnetic resonance cholangiopancreatography. Endoscopic retrograde cholangiopancreatography (ERCP) was mainly used as a therapeutic tool rather than a diagnostic tool. ERCP was used as a primary mode of treatment wherever feasible. Percutaneous biliary drainage was used in technically difficult cases. Results: Twenty-seven patients with symptomatic bile leak were identified in aforesaid period. Bile leak in 21 (77.88%) patients was due to postlaparoscopic cholecystectomy injury, while in 6 (22.22%) patients, it was associated with liver abscess. Major bile duct injury was seen in 10 patients with postcholecystectomy status and in 5 patients with liver abscess. Out of 27 cases, 25 (92.59%) were treated with ERCP and 2 (7.40%) with percutaneous drainage. Surgery was not required in any of the patients. Sphincterotomy with stent placement for 6 weeks was effective in 23 (92%) patients, and only sphincterotomy was effective in 2 (8%) patients undergoing ERCP. There was no mortality due to bile leak. Conclusion: Most patients presenting with bile leak including major bile duct injury without complete bile duct transection can be successfully treated by endoscopic therapy without the need for surgery.
Keywords: Bile leak; laparoscopic cholecystectomy; therapeutic endoscopic retrograde cholangiopancreatography